The Russian-Orthodox Tradition and Modernity - Buss, Andreas E. (Numen Book Series, 2003)
The book attempts to identify the uniqueness of the Russian-Orthodox religious tradition and to contrast it with two of the characteristics of modern Western society: its particular economic ethics and individualism. Max Weber and Louis Dumont provide the theoretical framework. The first part of the analysis is concerned with the economic ethics among Orthodox Russians, Old Believers and the adherents of various sects in the historical context of Russian society. The second part centres on the place and the kind of individualism in the Orthodox tradition since its beginnings in early monasticism and up to the twentieth century. The comparative perspective does not only shed new light on Russia but also on the development of Western individualism and on the Janus-like features of a traditional culture exposed to modernization.